A blood pressure clinic in a developing country. Issue 696 (October 1983) - Ahmed, M. E.
Abstract : There are few studies of hypertension in Sudan. In this report, 124 patients attending a newly established hypertension clinic are studied, most of whom were taking irregular treatment initially. Seventy-three (59%) had a strong family history of hypertension. There was a very low incidence of cigarette smoking (13.7%), and alcohol consumption (4.8%). As with blacks in the U.K. and the U.S.A., the commonest complications were cerebrovascular accidents and congestive cardiac failure. Most of the patients had moderately elevated blood pressures on the first visit, which fell significantly after 3 and 6 months of clinic attendance. Methyldopa and thiazides were the commonest drugs used, but a small pilot survey demonstrated that beta-blockers were effective. The high cost and poor availability of drugs contribute to poor compliance in these patients.